Value of texture analysis based on enhanced MRI for predicting an early therapeutic response to transcatheter arterial chemoembolisation combined with high-intensity focused ultrasound treatment in hepatocellular carcinoma. Issue 8 (August 2018) - Yu, J.Y.; Zhang, H.P.; Tang, Z.Y.; Zhou, J.; He, X.J.; Liu, Y.Y.; Liu, X.J.; Guo, D.J.
Abstract : Aim: To evaluate the potential value of texture analysis (TA) based on contrast-enhanced magnetic resonance imaging (MRI) for predicting an early response of patients with hepatocellular carcinoma (HCC) who were treated with transcatheter arterial chemoembolisation (TACE) combined with high-intensity focused ultrasound (HIFU). Materials and methods: Patients with HCC (n=89) who underwent contrast-enhanced MRI at 1.5 T 1 week before and 1 week, 1 month, and 3 months after TACE/HIFU were included in this retrospective study. Early responses were evaluated by two radiologists according to the Response Evaluation Criteria in Cancer of the Liver (RECICL). An independent Student's t -test and the Mann–Whitney U -test were used to compare the TA parameters between the complete response (CR) group and the non-complete response (NCR) group. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the predictive value of the NCR lesions. Results: Among the 89 patients, 58 showed CR and 31 showed NCR. Before TACE/HIFU, the CR group showed higher uniformity and energy but lower entropy than the NCR group ( p< 0.05). After TACE/HIFU, the CR group showed higher uniformity and energy but lower entropy and skewness than the NCR group ( p< 0.05). The logistic regression and ROC curve analyses showed that the entropy before TACE/HIFU and the skewness and entropy 1 week after TACE/HIFU were predictors of an early response. Conclusion: TA parameters based on contrast-enhanced MRI images 1 week before and after TACE/HIFU may act as imaging biomarkers to predict an early response of patients with HCC. Highlights: Complete response lesions showed lower heterogeneity pre-operation. Complete response lesions showed lower heterogeneity post-operation. Higher preoperative entropy could predict the non-complete response. Higher postoperative skewness and entropy could predict the non-complete response.